Pola Pergerakan Harga Saham dan Tingkat Likuiditas Saham pada Pengumuman Bonusshare: Studi Empiris pada Thin Market - Indah Kurniawati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2007)
The objective of this study is to investigate effect of public announcement- bonusshare- on market reaction in the Jakarta Stock Exchange. Since the trade condition in the Jakarta Stock Exchange is still a non-synchronous trading, therefore, this study employs a research method which is appropriate for such market.The sample consists of 54 companies which announce bonusshare from 1994-1996. The market reaction is measured using the Single Index Model and beta bias is corrected using Fowler and Rorke Method (1983) with four lags and four leads. Comparison of stock liquidity before and after the Bonusshare made use of wilcoxon signed ranks test and one sample kolmogorof smirnof test for data normality testThe result of this research shows that bonusshares announcement is positively responded statistically but not significantly responded by the market around the date of bonusshares announcement. The difference between stock liquidity before and after the bonusshares is insignificant except trading volume.Keywords: bonusshare, market reaction, stock liquidity